Student-teacher conferences and video-recorded microteaching sessions in developing pre-service teachers' teaching competences - Saiful Marhaban; Usman Kasim; Arifin Syamaun; Teguh Sulistyo (Studies in English Language and Education, 2023)
The present study highlighted the importance of pre-service teachers’ teaching competences in English Language Teaching (ELT). Facts show that empowering pre-service teachers is very important, but inspiring lecturers to implement a suitable teaching model takes time. Thus, this study aimed to determine how student-teacher conferences and video-recorded microteaching sessions (VRMS) affected pre-service teachers’ competences. Besides, the self-reflection of the pre-service teachers after watching their own teaching performance video and the conference with the lecturer was also investigated to see their behaviors towards their teaching performances. This mixed-method study involved one group and applied three main instruments to collect data: interviews (student-teacher conferences), checklists of teacher self-evaluation forms, and teaching practicum performance tests using a scoring rubric adapted from Brown (2000). There were 20 participants who were taking the Microteaching Course at the Department of English Education, Universitas Syiah Kuala, Banda Aceh, Indonesia. The study was conducted in one consecutive semester consisting of 16 meetings, each of which was 200 minutes long (4 credits). The results proved that student-teacher conferences and VRMS stimulated pre-service teachers’ teaching competences. Pre-service teachers grew their self-reflection after watching their own teaching videos and understood their strengths and weaknesses after getting student-teacher conferences. It implies that the improvement of their teaching competences resulted from a process involving the willingness to do self-reflection and the lecturer’s help in understanding what areas the pre-service teachers had to improve. The implications of the study are also presented and discussed in this paper.